Effect of Medical Ozone on Pain and Mouth Opening after Third Molar Surgery: Case Report - , Poliana Lima Bastos; , Mara Kelly Pinheiro Brito; , Calebe Lamonier de Oliveira Costa Paiva; , Diana Cristina Aguiar Freire; , Matéus Simplício Araújo; , Joelson Pessoa Dantas; , Antônio Evandro de Sousa Silva; , Nara Andre Diniz; , Eduardo Adelmo Alves Silva; , Mariana Linhares Farias; , Marcelo Bonifácio da Silva Sampieri; , Guilherme Salles Ottoboni (Archives of Current Research International, 2024)
Objectives: The aim of this study was to evaluate the efficacy of ozone therapy in reducing pain and its effect on mouth opening after third molar surgery. Case Presentation: The cases reported in this paper are part of a randomized, triple-blind, "split-mouth" clinical study, where surgery was performed using the conventional technique on one side (G1- Control Group), and using ozone therapy on the other side (G2- Test Group), as a means of comparison. In this study, five patients were selected with indications for bilateral extraction of lower third molars with similar positions, and who did not present characteristics of infection. In the immediate preoperative period, pain levels were assessed using the VAS scale and mouth opening using a pachymeter; this was repeated in the immediate postoperative period and after 72 hours. The patient's perception of pain, mouth opening and analgesic intake were assessed. Results: Ozone therapy (G2) reduced postoperative pain, reduced the intake of analgesics and achieved better control of mouth opening when compared to the conventional technique (G1). Conclusion: Ozone therapy can be an effective, biocompatible and safe alternative for pain control and mouth opening after third molar surgery, helping to improve patients' quality of life and bringing new perspectives to dentistry. However, due to the small sample size, it is very important to carry out more clinical studies on the subject.